The impacts of Val158Met in Catechol-O-methyltransferase (COMT) gene on moral permissibility and empathic concern. (1st February 2017) - Ru, Wenzhao; Fang, Pengpeng; Wang, Bei; Yang, Xing; Zhu, Xu; Xue, Mengying; Shen, Guomin; Gao, Xiaocai; Gong, Pingyuan
Abstract: Dopamine levels in the brain influence emotional experiences and empathic responses to others' misfortune. Inspired by roles of Catechol- O -methyltransferase (COMT) in dopamine degradation and the link between moral judgment and empathic responses, this study investigated to what extent the Val158Met polymorphism of COMT gene contributes to individual differences in moral permissibility and empathic dispositions. One thousand two hundred and seventy-two Chinese Han college students, who were differentiated with the COMT Val158Met (rs4680) polymorphism, rated permissibility of harm in moral dilemmas and scored their empathic dispositions with Interpersonal Reactivity Index. The results showed a significant association between COMT Val158Met and the moral permissibility of committing harm. Individuals with the Val/Val genotype, which is associated with lower levels of dopamine, endorsed impersonal harm as more impermissible than those with the Val/Met and Met/Met genotypes. Results also showed that individuals with the Val/Val genotype showed higher empathic concern for others' misfortune. The findings provide the first evidence for the link between COMT gene and the moral permissibility, highlighting the roles of dopamine in social cognition. Highlights: COMT Val158Met modulates on moral permissibility and empathic concern. Individuals with Val/Val genotype endorse impersonal harm as more impermissible. Individuals with Val Val/Val genotype show higher empathic concern.